2022
DOI: 10.3390/life12060884
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Activity of Ixodes ricinus Females in 900 MHz Electromagnetic Field

Abstract: Mobile telecommunications technologies have become an indispensable part of people’s lives of all ages around the world. They affect personal life and social interactions and are a work tool in the work routine. Network availability requirements and the quality of the Internet connection are constantly increasing, to which telecommunications providers are responding. Humans and wildlife live in the permanent presence of electromagnetic radiation with just a minor knowledge of the impact this radiation has. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Some studies reported no significant changes in the locomotor activity of animals exposed to RF radiation in different frequencies range (e.g., rats exposed to 1.2 GHz [ 29 ], 905-MHz [ 30 ], and 900 MHz [ 31 ], and mice exposed to 1950 MHz [ 32 ]), while others report a decrease in the locomotor activity (in rats exposed to 2.5 GHz RF radiation [ 33 ] and 900 MHz radiation [ 34 ]. There are also data suggesting RF-exposed animals have higher locomotor activity [ 35 , 36 ]; our results linking RF exposure with increased locomotor activity support these latter findings.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies reported no significant changes in the locomotor activity of animals exposed to RF radiation in different frequencies range (e.g., rats exposed to 1.2 GHz [ 29 ], 905-MHz [ 30 ], and 900 MHz [ 31 ], and mice exposed to 1950 MHz [ 32 ]), while others report a decrease in the locomotor activity (in rats exposed to 2.5 GHz RF radiation [ 33 ] and 900 MHz radiation [ 34 ]. There are also data suggesting RF-exposed animals have higher locomotor activity [ 35 , 36 ]; our results linking RF exposure with increased locomotor activity support these latter findings.…”
Section: Discussionsupporting
confidence: 88%
“…Female I. ricinus ticks tested in the same manner did not display any significant affinity for either arm. However, tracking ticks' movement in the circular arena with irradiated and shielded parts revealed the difference in the movement dynamics [45].…”
Section: Discussionmentioning
confidence: 98%
“…Behavior in the field depends on many variables; therefore, a number of behavioral studies are carried out in laboratory conditions. Locomotor activity [ 50 , 51 , 52 ], questing behavior [ 53 ], influence of hydration on behavior [ 54 , 55 ], and repellent reactions [ 56 , 57 ] are among the behavior types that have been studied the most. The majority of research focuses on monitoring tick–stimulus response [ 51 , 54 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Locomotor activity [ 50 , 51 , 52 ], questing behavior [ 53 ], influence of hydration on behavior [ 54 , 55 ], and repellent reactions [ 56 , 57 ] are among the behavior types that have been studied the most. The majority of research focuses on monitoring tick–stimulus response [ 51 , 54 , 57 , 58 , 59 , 60 ]. Apparatuses that are designed to test locomotor behavior and influence of hydration commonly have horizontal and vertical sections and wet areas [ 25 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%